Perlindungan dan Pemenuhan Hak Anak (Balita) Atas Kesehatan terhadap Bahaya Asap Rokok - Yuliana Primawardani (Badan Strategi Kebijakan Hukum, 2012)
Every child has the right to health. Nonetheless, not all children's right can be fulfilled if the people around them do not have the awareness to stop smoking or to smoke in a designated place. The dangers of cigarette smoke will not only cause disease to the children, but the fetus in the womb will be affected by the negative impact of cigarettes. Various rules applied are yet to be effective as there is no strict sanctions for violations conducted. Therefore, it requires the government's attention so that the rights of children to health can be met.